2018
DOI: 10.1016/j.ajog.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Trends in patient procurement of postoperative opioids and route of hysterectomy in the United States from 2004 through 2014

Abstract: Opioid prescriptions filled for postoperative pain after hysterectomy substantially increased from 2004 through 2014. Opioid prescription procurement has increased despite a concomitant increase in minimally invasive hysterectomy routes. In light of the current opioid epidemic, physicians must recognize that postoperative prescribing practices may contribute to chronic opioid use. Heightened awareness of opioid prescribing practices following surgery is critically important to decrease risk of development of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Gynecologic procedures account for 7.7% of all surgeries performed in women representing an important generator of opioid prescriptions 10 . Hysterectomy is the most common gynecologic surgery performed and the current literature largely explores opioid use exclusively for hysterectomy 5,9,[11][12][13] . Much less is known about opioid prescribing trends and rates of persistent use following non-hysterectomy gynecologic surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Gynecologic procedures account for 7.7% of all surgeries performed in women representing an important generator of opioid prescriptions 10 . Hysterectomy is the most common gynecologic surgery performed and the current literature largely explores opioid use exclusively for hysterectomy 5,9,[11][12][13] . Much less is known about opioid prescribing trends and rates of persistent use following non-hysterectomy gynecologic surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Expectations for no pain after surgery, as well as aggressive marketing to physicians from drug companies have led to increased use of opioids in the perioperative setting. For example, opioid prescriptions increased significantly from 2004 to 2014 in women undergoing hysterectomy for benign indications, even though less invasive techniques have emerged in recent years [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Thompson et al demonstrated an increase in opioid prescriptions after hysterectomy from 2004 to 2014, despite a concomitant increase in minimally invasive routes. 10 Our more recent time period of 2016 to 2019 suggests a shift in trends towards more judicious opioid prescribing among gynecologists. Alternatively, this may reflect cultural or individual physician practices at our institution.…”
Section: Resultsmentioning
confidence: 99%
“…9 Despite this, there are few evidenced-based guidelines informing gynecologic surgeon prescribing. 10 Enhanced recovery after surgery protocols encourage multimodal, opioid-sparing, postoperative pain-control and recommend prescribers account for patient factors when prescribing postoperative opioids, but explicit prescribing regimens and procedure specific recommendations are lacking. 11 This study seeks to contribute to the literature on opioid prescribing patterns after gynecologic surgery by focusing on laparoscopic sterilization.…”
Section: Introductionmentioning
confidence: 99%